Evaluation of vaccination coverage and the knowledge of parturient admitted for labor in a public tertiary maternity hospital in western São Paulo, Brazil - Panucci, Luís Antônio Gilberti; Sant’Anna Pinheiro, Luiza; Roque, João Pedro Teixeira; Flores, Edilson Ferreira; Giuffrida, Rogério; Prestes-Carneiro, Luiz Euribel (Frontiers in Public Health, 2025)
IntroductionVaccination coverage among pregnant women in Brazil remains poorly documented, particularly in low-resource settings. This study aimed to (1) assess the completeness of vaccine records on prenatal cards and (2) evaluate pregnant women’s knowledge of vaccines recommended by the Brazilian National Immunization Program (NIP).Methods: A cross-sectional study was conducted at the Hospital Estadual de Presidente Prudente (HEPP), a public secondary hospital in São Paulo, Brazil, between August 2022 and April 2023. The study population comprised 1,130 women admitted for delivery, of whom 541 (47.9%) had prenatal cards available for review. Postpartum, data from the prenatal cards were extracted, and participants completed a structured questionnaire to assess their vaccine knowledge. Sociodemographic data were obtained from electronic medical records. Univariate analyses were performed using Pearson’s Chi-Squared or Fisher’s Exact Test. Only 11.2% of the reviewed prenatal cards documented complete vaccination with all four NIP-recommended vaccines, while 31% contained no vaccine records at all. The tetanus, diphtheria, and acellular pertussis (Tdap) vaccine had the highest documented coverage (61%). The mean age of participants was 27.1 ± 0.3 years. Although most participants (91.1%) believed they had been vaccinated during pregnancy, only 61.5% could specify which vaccines they had received. No significant association was found between sociodemographic factors and the completeness of vaccine documentation. The low level of vaccination documentation and the critical knowledge gaps identified in this study highlight deficiencies in the quality of prenatal care within Brazil’s Unified Health System (SUS) in the Western region of São Paulo state. Addressing these issues requires concerted efforts to improve healthcare provider training, strengthen public health education, and standardize documentation practices.